EFFECTS OF SOAKING PRETREATMENT AND CITRIC ACID LINTNERIZATION ON THE PHYSICOCHEMICAL AND FUNCTIONAL PROPERTIES OF RED GUINEA CORN STARCH - Amusan, Temiloluwa O.; Nwaedozie, Jonathan M.; Faruruwa, Muhammad D.; Umoru, Patricia E. (FUDMA Journal of Sciences, 2026)
This study investigated the influence of pretreatment and citric acid lintnerization on the physicochemical and functional properties of Red Guinea corn starch. Cereal grains were soaked at room temperature for varied durations (0 h, 24 h and 48 h) before starch isolation, after which the starch was subjected to citric acid lintnerization at different concentrations (1 M, 3 M and 5 M). The effects of soaking time were evident in the subsequent esterification process, with prolonged soaking enhancing solubility (% S) and Paste clarity (%PC) while reducing swelling power (SP) and water holding capacity (WHC). SP decreased from 10.89 ±1.13 g/g in unsoaked crude starch (U‑CS) to 5.33 ±0.35 g/g in 5 M lintnerized starch subjected to 48 hours soaking (S48‑M5). Solubility increased with increase in citric acid concentration, reaching 32.00±11.1% in S48‑M5 compared to 8.00±0.0% in unsoaked crude starch (U‑Cs). Similarly, paste clarity increased with prolonged lintnerization, from 23±0.00% in U‑CS to 59±0.00% in S48‑M5. FTIR analysis confirmed the presence of a new peak at 1718 cm-1, which is attributed to the presence of C=O carbonyl stretches of ester. Also, there is a sharp peak at 1541 cm-1 which is attributed to C-O-C stretch of ester. Which were absent in the spectra structure of the crude starches. The degree of substitution increases (from 0.5427±0.00 to 0.7817±0.00) with increase in citric acid concentration. These findings demonstrate that soaking pretreatment alters starch granule accessibility and reactivity, thereby intensifying the effects of citric acid lintnerization.